Can pragmatic research, real-world data and digital technologies aid the development of psychedelic medicine?. (January 2022) - Carhart-Harris, Robin L; Wagner, Anne C; Agrawal, Manish; Kettner, Hannes; Rosenbaum, Jerold F; Gazzaley, Adam; Nutt, David J; Erritzoe, David
Favourable regulatory assessments, liberal policy changes, new research centres and substantial commercial investment signal that psychedelic therapy is making a major comeback. Positive findings from modern trials are catalysing developments, but it is questionable whether current confirmatory trials are sufficient for advancing our understanding of safety and best practice. Here we suggest supplementing traditional confirmatory trials with pragmatic trials, real-world data initiatives and digital health solutions to better support the discovery of optimal and personalised treatment protocols and parameters. These recommendations are intended to help support the development of safe, effective and cost-efficient psychedelic therapy, which, given its history, is vulnerable to excesses of hype and regulation.